A case of nonvalvular endocarditis with biventricular apical infected thrombi. Issue 7 (12th July 2020) - Vani, Anish; Ahluwalia, Monica; Donnino, Robert; Jung, Albert; Vaynblat, Mikhail; Latson, Larry; Saric, Muhamed
Abstract: We report what appears to be the first case of biopsy‐proven nonvalvular endocarditis with biventricular apical infected thrombi. A 47‐year‐old man presented with hypoxic respiratory failure from a multilobar pneumonia due to methicillin‐resistant Staphylococcus aureus (MRSA). Transthoracic echocardiography and cardiac magnetic resonance imaging revealed biventricular apical masses suggestive of nonvalvular endocarditis with infected thrombi. Given concern for ongoing septic embolization to the lungs and brain despite appropriate antimicrobial therapy, the masses were surgically resected. Culture and histopathology confirmed MRSA‐positive infected thrombi. In this case report, we highlight the differential diagnosis of apical masses and the role of multimodality imaging.